Effects of transcranial direct current stimulation on modulating executive functions in healthy populations: a systematic review and meta-analysis - You, Guopeng; Pan, Xinliang; Li, Jun; Zhao, Shaocong (Frontiers in Human Neuroscience, 2024)
BackgroundConventional research has asserted that cognitive function, particularly, response inhibition, is closely related to the inferior frontal cortex (IFC), dorsolateral prefrontal cortex (DLPFC), or orbital frontal cortex (OFC), which belong to the prefrontal cortex (PFC). Different targets of anodal or cathodal transcranial direct current stimulation (a-tDCS or c-tDCS) would affect the experimental results, but the stimulation of the same brain target would produce inconsistent findings.PurposeThis study aimed to investigate the effects of a-tDCS and c-tDCS applied over the PFC for healthy populations on reactive and proactive control process compared with sham or no tDCS conditions, as assessed using the Stop-signal task (SST) and Go/NoGo (GNG) task performance.MethodsThis systematic review was performed following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Search was conducted on Web of Science, Google Scholar, PubMed, Elsevier, Scopus, and Science Direct until March 2024. Studies that assessed the inhibitory control in SST or/and GNG tasks were included to achieve a homogenous sample.ResultsFourteen studies were included for meta-analyses, which were performed for two outcome measures, namely, stop-signal reaction time (SSRT) and commission error (CE) rate. A-tDCS and c-tDCS over the PFC had significant ergogenic effects on SST performance (mean difference = −17.03, 95% CI [−24.62, −9.43], p < 0.0001; mean difference = −15.19, 95% CI [−19.82, −10.55], p < 0.00001), and that of a-tDCS had a positive effect on GNG task performance (mean difference = −1.42, 95% CI [−2.71, −0.14], p = 0.03).ConclusionThis review confirmed the engagement of PFC tDCS in reactive and proactive inhibitory processes. Future research should increase sample size and implement personalized stimulus protocols.